PRO-EEL Brochure: towards reproduction and a self-sustained aquaculture of european eel - Jonna Tomkiewicz (Zenodo, 2010)
The aim of the PRO-EEL project is to breed the European eel (Anguilla anguilla) in captivity. Eel reproduction has become a crucial area of research due to a severe decline in the natural stock, resulting in an urgent need to shift from capture-based aquaculture to the breeding of eels for a self-sustainable aquaculture. The aim of the PRO-EEL project is to breed the European eel (Anguilla anguilla) in captivity. Eel reproduction has become a crucial area of research due to a severe decline in the natural stock, resulting in an urgent need to shift from capture-based aquaculture to the breeding of eels for a self-sustainable aquaculture.